Extension of ImageNotion to Allow Privacy-Aware Image Sharing - Walter, Andreas; Nagypal, Gabor (Computing and Informatics, 2012)
A growing number of users in Web 2.0 based social network sites and photo sharing portals upload millions of images per day. In many cases, this leads to serious privacy threats. The images reveal not only the personal relationships and attitudes of the user who uploads the images, but those of other persons displayed in the images as well. In this paper, we propose a system architecture for privacy-aware image sharing. Our approach is based on the ImageNotion application, which combines automated processes to create high-quality semantic image annotations.